Bimbingan Keagamaan dalam Membina Kemandirian Anak di Panti Asuhan Tunas Bangsa Kota Solok - Fitri, Adella Hafifah; Syawaluddin, Syawaluddin (Lembaga Yasin AlSys, 2023)
Religious guidance is a process of providing appropriate assistance by mentors so that children can increase their piety through religious approaches. The religious approach is a container for fostering independence with good directions in accordance with the commands of Allah SWT so that children understand independence for a better future. The background of this research is considering the number of children who are less independent so that it becomes an obstacle in every action. Because nowadays educating children to be independent, it is necessary to use a religious approach so that children are independent in all things and teach children to always be guided by religious teachings. The use of this religious approach must be applied to children from an early age because religious development takes quite a long time so that the goals can be achieved properly. In this study using descriptive qualitative research. In this study it was revealed that the religious approach is very influential on the independence of children today. In this sophisticated era, children must be equipped with religious knowledge to guide children in the future. An independent child who is equipped with religious knowledge will be different from a child who is independent but is not equipped with religious knowledge. From the results of religious guidance carried out at the Tunas Bangsa Orphanage, it was able to show quality personality changes that were in accordance with religious rules.